Determinants of Modern Agricultural Technology Adoption for Teff Production: The Case of Minjar Shenkora Woreda, North Shewa Zone, Amhara Region, Ethiopia - Abebaw Hailu Fikire; Girma Mulugeta Emeru (Advances in Agriculture)
Agriculture is one of Ethiopia’s economic cornerstones, although its production remains low. Since then, the implementation of modern agricultural technologies has remained a promising strategy in Ethiopia for increasing agricultural production, achieving food security, and reducing poverty. The objective of the study is to examine the determinants of modern agricultural technology adoption for teff production in Minjar Shenkora woreda. The data were collected from the representatives of 362 rural households. This study employed both descriptive statistics and multinomial logit model. The estimations of the multinomial logit model revealed that sex, age, marital status, tropical livestock units, educational level of household head, distance to market, extension contact, active household members, access to credit, off-farm activities participation, and cultivated land size are the determinants of modern agricultural technology adoption for teff production in Minjar Shenkora woreda, North Shewa Zone, Amhara Region, Ethiopia. Therefore, this study recommended that the country’s federal and regional governments, agricultural development offices, nongovernmental organizations, and donor agencies should collaborate with farm households to improve access to information, access to credit, encourage off-farm participation and provide training and consulting services to increase the adoption of modern agricultural technologies.